PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP TURNOVER INTENTION - Putra, Dewa Made Bayu Adi; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2019)
This study aim was to determine the effect of turnover intention on job stress and work motivation, and the role of job satisfaction in mediating the effect of turnover intention on job stress and work motivation at Nirmala Plaza Supermarket Jimbaran employee. The sample amounted to 34 employees with the saturated sampling method. Questionnaires were used as data collection techniques with survey approaches and then data were analyzed with SEM-PLS. The results show that there is a positive and significant effect of job stress on turnover intention, while there is a negative and significant effect of work motivation and job satisfaction on turnover intention. In addition, the results of the analysis also show that the effect of job stress and work motivation on turnover intention was mediated by job satisfaction partially. The management of Nirmala Plaza Supermarket Jimbaran needs to reduce employee job stress and increase work motivation along with the job satisfaction to reduce the turnover intention. Keywords: work motivation, job stress, job satisfaction, turnover intention